Emerging Trends and Research Foci in Tumor Microenvironment of Pancreatic Cancer: A Bibliometric and Visualized Study - Wu, Kaiwen; Liu, Ye; Liu, Lei; Peng, Yunlan; Pang, Honglin; Sun, Xiaobin; Xia, Demeng (Frontiers in Oncology, 2022)
Background Pancreatic cancer (PC) is a serious disease with high mortality. The tumor microenvironment plays a key role in the occurrence and development of PC. The purpose of this study is to analyze trends by year, country, institution, journal, reference and keyword in publications on the PC microenvironment and to predict future research hotspots. Methods The Web of Science Core Collection was used to search for publications. We analyzed the contributions of various countries/regions, institutes, and authors and identified research hotspots and promising future trends using the CiteSpace and VOSviewer programs. We also summarized relevant completed clinical trials. Results A total of 2,155 papers on the PC microenvironment published between 2011 and 2021 were included in the study. The number of publications has increased every year. The average number of citations per article was 32.69. The USA had the most publications, followed by China, and a total of 50 influential articles were identified through co-citation analysis. Clustering analysis revealed two clusters of keywords: basic research and clinical application. The co-occurrence cluster analysis showed glutamine metabolism, carcinoma-associated fibroblasts, oxidative phosphorylation as the highly concerned research topics of basic research in recently. The three latest hot topics in clinical application are liposomes, endoscopic ultrasound and photodynamic therapy. Conclusion The number of publications and research interest have generally increased, and the USA has made prominent contributions to the study of the tumor microenvironment of PC. The current research hotspots mainly focus on energy metabolism in the hypoxic tumor microenvironment, cancer associated fibroblasts in regulating the tumor microenvironment, accurate diagnosis, drug delivery and new treatments.